Negative prognostic impact of right ventricular free wall strain in patients with functional mitral regurgitation undergoing transcatheter edge-to-edge repair. (4th February 2022) - Iuliano, G; Silverio, A; Bellino, M; Esposito, L; Di Feo, F; Cristiano, M; Radano, I; Provenza, G; Galasso, G; Baldi, C; Citro, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Backgrounds: although right ventricular (RV) systolic dysfunction seems to be associated with adverse outcome after transcatheter edge-to-edge mitral valve repair (TEER) with the MitraClip system, the prognostic value of RV free wall strain in this setting has not been yet investigated.  Purpose: aim of this study is to evaluate RV free wall strain as predictor of outcome in patients with severe or moderate-to-severe functional MR undergoing TEER and its prognostic role compared with tricuspid annular plane systolic excursion (TAPSE). Methods: 102 patients [73 (IQR 66.8-77.0) years, 73 males (71.6%)] were retrospectively selected from March 2012 to February 2021. Echocardiograms were performed by using General Electric machines. RV free wall strain was assessed through RV modified apical 4-chamber view, setting the region of interest to minimum size (Figure 1). Values of RV free wall strain >-20% were recognized as abnormal. We considered a composite endpoint including rehospitalization for heart failure (HF) and overall death as primary outcome. Secondary outcomes were overall death, cardiac death and rehospitalization for HF. All patients were assessed at the longest available follow-up [median 22.1 (IQR 9.7-49.3) months]. Results: primary outcome was found in 60 (58.8%) patients, while secondary outcomes, i.e. overall death, cardiac death and rehospitalization for HF, were found respectively in 50 (50.0%), 31 (30.4%) and 36 (35.3%) patients. Mean TAPSE was 16.7 ± 4.0 mm and mean RV free wall strain was -16.9 ± 6.0%. At univariable analysis both TAPSE (HR 0.907, CI 0.848-0.970, p value 0.004) and RV free wall strain (HR 0.937, CI 0.897-0.979, p value 0.004) were significantly associated with the primary outcome. Kaplan-Meier survival curves showed that patients with TAPSE <17 mm had a lower survival free from the composite outcome compared with those with TAPSE ≥17 mm (Log-Rank = 0.030); patients with RV free wall strain value > -20% also showed a lower survival free from the composite outcome compared with patients with RV free wall strain ≤-20% (Log Rank 0.004). Among patients with preserved RV systolic longitudinal function as indicated by TAPSE ≥17 mm, subjects with RV free wall strain >-20% had a significantly higher incidence of the composite outcome compare with those with RV free wall strain ≤-20% (Log-Rank = 0.008, Figure 2). Conversely, no difference was found among patients with TAPSE <17 mm.  Conclusions: RV dysfunction assessed either by TAPSE and RV free wall strain is associated with poorer outcome in patients with severe or moderate-to-severe functional MR undergoing TEER. Compared with TAPSE, RV free wall strain seems to be superior in identifying patients at higher risk of adverse events during follow-up. Our data encourage the use of this speckle tracking-derived echocardiographic parameter in routinely evaluation of patients with functional MR candidate for TEER.